2016
DOI: 10.2217/nnm-2015-0014
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Assessment of Magnetically Actuated Biomaterials and Prospects in Tendon Healing

Abstract: Magnetically actuated biomaterials have potential to modulate inflammation and the growth of fibrous tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Indeed, protein expression of tendon‐related ECM proteins (collagen type I and tenascin C) was found to be increased under magnetically stimulated (2 Hz, 350 mT) adipose‐derived stem cells cultured on aligned fibrous magnetic scaffold (0.018:1 w/w MNPs in PCL‐based blend), therefore suggesting the tenogenic commitment of this cell population (Gonçalves et al, ). Furthermore, subcutaneous implantation of the same biomaterial formulation of PCL‐based blend magnetically responsive membrane (0.018:1 w/w MNPs) in a rat model has shown its ability to moderate inflammation (Santos et al, ). The presence of M2 macrophages (anti‐inflammatory phenotype) in the fibrous tissue was reduced and the magnetically responsive membrane also prevented mast cell infiltration and fibrous tissue thickening over time (9 weeks) (Santos et al, ).…”
Section: Beyond Repair: Shooting For Regenerationmentioning
confidence: 99%
“…Indeed, protein expression of tendon‐related ECM proteins (collagen type I and tenascin C) was found to be increased under magnetically stimulated (2 Hz, 350 mT) adipose‐derived stem cells cultured on aligned fibrous magnetic scaffold (0.018:1 w/w MNPs in PCL‐based blend), therefore suggesting the tenogenic commitment of this cell population (Gonçalves et al, ). Furthermore, subcutaneous implantation of the same biomaterial formulation of PCL‐based blend magnetically responsive membrane (0.018:1 w/w MNPs) in a rat model has shown its ability to moderate inflammation (Santos et al, ). The presence of M2 macrophages (anti‐inflammatory phenotype) in the fibrous tissue was reduced and the magnetically responsive membrane also prevented mast cell infiltration and fibrous tissue thickening over time (9 weeks) (Santos et al, ).…”
Section: Beyond Repair: Shooting For Regenerationmentioning
confidence: 99%
“…Additionally, the application of an external magnetic field can be explored toward enhancing the maturation of tissue engineered constructs in vitro prior to implantation. Thus, we have been exploring the use of lower frequencies to understand the potential role of these magnetic field settings as a mechanical stimulus on human cells 15 – 17 . For instance, in a previous work, we have demonstrated that the application of a low-frequency magnetic field promoted tenogenic differentiation of human adipose stem cells cultured on aligned magnetic scaffolds by enhancing the deposition of tendon-like ECM (collagen type I and tenascin C) 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, magnetic stimulus may act synergistically with magnetizable nanoparticles internalized by cells in AQ 10 K30344_C010.indd 287 05/29/18 2:55:49 PM culture or embedded within 3D scaffolds creating local forces, which can be physically sensed by cells assisting mechanotransduction processes that will ultimately lead to an in vitro maturation of the cell-laden constructs prior to implantation. This approach has been previously hypothesized and reported by our group on the use of magnetic bioreactors in the stimulation of stem cells towards tenogenic, osteogenic, or chondrogenic differentiation (Lima et al 2015, Santos et al 2016 and by others for osteogenesis (Meng et al 2013, Kang et al 2013, cardiac TE (Sapir et al 2014), and neuronal regeneration (Antman-Passig and She 2016). 3D-printed magnetic scaffolds cultured with hASCs exposed to oscillation frequency conditions provided by a magnefect-nano transfection device (nanoTherics Ltd, UK) showed that magnetic stimulation tend to accelerate the production of collagen and noncollagenous proteins by cells after seven days (Goncalves et al 2016).…”
Section: Magnetic Stimulationmentioning
confidence: 95%
“…On the other hand, magnetic responsive membranes, which were implanted subcutaneously in rats exposed to a pulsed electro-magnetic eld (PEMF) waveform with a magnetic eld intensity peak of 0.01 T, a duty cycle of 6.3 ms and a frequency of 75 Hz for 2 hours a day, ve days a week (Magnum XL Pro, Globus), showed to modulate tissue in ammatory response, translated by a decrease in the number of mast cells in ltration and reduction of the thickness of the brous capsule (Santos et al 2016). The coils that provided the mechano-magnetic stimulation within a therapeutic mat were placed under the animals' cage.…”
Section: Magnetic Stimulationmentioning
confidence: 99%